Developing Snake and Ladder Game to Teach Vocabulary on Recount Text for Eighth Grade Students at MTs Syekh Subakir 2 Sumberasri - Namyra Alvatikha Pratiwi; Ahmad Saifudin; Tyas Alhim Mubarok (Journey: Journal of English Language and Pedagogy, 2023)
The purpose of this research is to create a snake and ladder game to educate eighth grade students at Mts Syekh Subakir 2 Sumberasri vocabulary on recount texts. The R&D Method was used by the researcher to conduct this study. So research and development methods are methods that produce, develop and test the effectiveness of a product. The design and creation of snake and ladder media resulted in a media validation questionnaire from experts as proof that snake and ladder media in this study is suitable for use as a medium for teaching recount text vocabulary to eighth grade students of Syekh Subakir 2 Sumberasri. This research was conducted to find problems experienced by eighth grade students in English lessons and provide solutions to these problems. In eighth grade Syekh Subakir 2 Sumberasri, the researcher found a problem with students, namely a lack of vocabulary knowledge, which hindered the learning process. Therefore, the researcher created snake and ladder game media as an English learning media so that students were motivated to learn vocabulary.